2014
DOI: 10.3390/nu6125636
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Absorption from Micronutrient Powder Is Low but Is not Affected by Iron in Kenyan Infants

Abstract: Interference with zinc absorption is a proposed explanation for adverse effects of supplemental iron in iron-replete children in malaria endemic settings. We examined the effects of iron in micronutrient powder (MNP) on zinc absorption after three months of home fortification with MNP in maize-based diets in rural Kenyan infants. In a double blind design, six-month-old, non-anemic infants were randomized to MNP containing 5 mg zinc, with or without 12.5 mg of iron (MNP + Fe and MNP − Fe, respectively); a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…The results of our study support the limited research that shows no evidence that consumption of foods fortified with Fe has a negative effect on Zn absorption (30,32) or Zn status (32,33) in young children. The absorption of Zn from the study formulae was similar to that previously reported in infants (36) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of our study support the limited research that shows no evidence that consumption of foods fortified with Fe has a negative effect on Zn absorption (30,32) or Zn status (32,33) in young children. The absorption of Zn from the study formulae was similar to that previously reported in infants (36) .…”
Section: Discussionsupporting
confidence: 89%
“…Whether Fe supplements given alone compromise infant Zn nutrition is still unclear (21,(27)(28)(29) . When present as a fortificant, Fe does not appear to inhibit Zn absorption (30)(31)(32) , impair Zn status (32)(33)(34) or result in measurable circulating non-transferrin-bound Fe (16) . Few studies, however, have addressed this in infants.…”
mentioning
confidence: 99%
“…The data originated from studies of zinc absorption in 262 infants and children conducted in poor, rural communities mostly in economically developing countries (China, India, Kenya, Malawi, and Zambia) (10)(11)(12)(13)(14)(15)(16) and in a westernized, resource-adequate community in the United States (17) ( Table 1). The subjects were apparently healthy, with no chronic illnesses or conditions affecting zinc absorption.…”
Section: Methodsmentioning
confidence: 99%
“…For example, biomarkers specific to intestinal inflammation would be of particular interest in addition to CRP, which reflects systemic inflammation. The highly prevalent condition of environmental enteropathy has been proposed to have a negative impact on zinc absorption (11,38,39). From the coefficients of determination of the statistical models it was apparent that the models generally accounted for no more than 50-60% of the variance of TAZ, which is typical of modeling of individual data from stable-isotope studies of human nutrition.…”
Section: Figurementioning
confidence: 99%
“…Although a similar "master regulator" analogous to hepcidin has not been identified for other micronutrients, data are emerging to suggest adverse effects of environmental enteric dysfunction and inflammation on zinc absorption and homeostasis. 13,46,47 Another mechanism by which disrupted gut health may impact development is through alterations in the gut microbiota which, through interaction with the developing innate immune system, can drive elevations in proinflammatory and antiinflammatory cytokines and influence brain function. 48 Such early and enduring inflammatory stimuli have also been linked to a risk of systemic metabolic disease associated with later noncommunicable diseases, particularly in settings where access to more abundant caloric intake is emerging.…”
Section: The Interaction Of Nutrition Inflammation Neurodevelopmentmentioning
confidence: 99%